A Pragmatic Utopia? Utopianisms and Anti-utopianisms in the Critique of Educational Discourse - Martin, Christopher (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
This paper seeks to address what I claim are competing utopian and anti-utopian impulses within educational discourse aimed at formulating a just and fair conception of public education. On the one hand, there is a tendency to prescribe concrete utopias – normative blueprints that claim to portent how a redeemed public education will (and ought to) be. On the other hand, there is the tendency to prescribe material revolutions – strategic blueprints that dictate the kinds of political action that educators must undertake in order to bring about lasting social change. I argue that both of these approaches to formulating a just conception of public education are flawed for pragmatic as well as normative reasons. As a way of avoiding the pitfalls inherent to utopianism and anti-utopianism, I suggest that those of us interested in a just conception of education maintain our focus on a kind of pragmatic utopianism. While pragmatic utopianism requires that we abandon the notion that we can ever know what a redeemed public education will look like in its particulars, it does set out standards of deliberation that can increase the likelihood that we will be able to address issues of educational justice as they arise.